Pattern of cytopenias & systemic immune-inflammation index among hospitalized patients of COVID-19 - Ambreen Kashif; Sadia Taj; Sidra Sonia Chaudhry; Saira Moin; Aijaz Zeeshan Khan Chachar; Ayaz Lone (Journal of the Pakistan Medical Association, 2024)
Objectives: To compare the extent of cytopenias and systemic immune inflammation index of hospitalised coronavirus disease-2019 patients during the first and second/third waves of the pandemic. Method: The retrospective, cross-sectional study was conducted in October 2021 at Fatima Memorial Hospital, Lahore, Pakistan, and comprised data of hospitalised coronavirus disease-2019 patients regardless of age and gender from May 2020 to June 2021. Data was segregated into first wave that lasted from May to July 2020, second wave that lasted from early November to mid-December 2020, and third wave that ranged from mid-March to June 2021. For comparison purposes, the data of first wave was in group A, while data of second and third waves was pooled into group B. Age, gender, comorbidities, requirement of ventilator support and outcome of the patients was noted. Inflammatory markers were compared on the basis of complete blood count and systemic immune-inflammation index data. Data was analysed using SPSS 25. Results: Of the 202 patients, 90(44.5%) were in group A and 112(55.4%) were in group B. There were 108(53.5%) males and 94(46.5%) females. The median age in males was 58 years (interquartile range: 21 years) and it was 56 years (interquartile range: 21 years) in females. Neutrophilia (p<0.001), leukocytosis (p<0.001) and lymphocytopenia (p<0.001) had direct association with increased systemic immune-inflammation. Raised systemic immune-inflammation also had an association with increased requirement of ventilator support (p=0.2) and increased mortality (p=0.001). There were more females, more critical patients, more patients with anaemia, leukopenia, lymphocytopenia and thrombocytopenia in group B compared to group A (p<0.05). Need for ventilator suppor and mortality were also higher in group B compared to group A (p<0.05). Conclusion: All the indicators analysed were worse during the second and third waves of coronavirus disease-2019 compared to the first wave of the pandemic. Key Words: COVID-19, Thrombocytopenia, Leukopenia, Lymphopenia, Cytopenia.